STUDI PERILAKU HARIAN MONYET EKOR PANJANG (Macaca fascicularis) DI KAWASAN HUTAN RESORT RANAMESE, TAMAN WISATA ALAM RUTENG, KABUPATEN MANGGARAI TIMUR, PROVINSI NUSA TENGGARA TIMUR - Marianus Dedi Dahar; Maria M. E. Purnama; Norman P.L.B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
This research is about the Study of the Daily Behavior of the Long Tailed Monkey (Macaca fascicularis) in the Forest Area of ​​the Ranamese Resort, Ruteng Nature Tourism Park, East Manggarai Regency, East Nusa Tenggara Province. The purpose of this study was to determine the daily behavior of long-tailed monkeys in the forest area of ​​Ranamese Resort, Ruteng Nature Tourism Park, East Manggarai Regency, East Nusa Tenggara Province. This research has been carried out during July-September 2020. The study began with collecting the location points of the long-tailed monkeys found using GPS Garmin 64S in three time periods with an interval of 2 hours, namely in period I (at 06.00/08.00 WITA), period II (at 10.00/12.00 WITA). , period III (15.00/17.00 WITA) accompanied by observations of the number of behaviors of long-tailed monkeys (Macaca fascicularis) using the focal animal sampling method. The data obtained were analyzed using non-parametric statistics with the Kruskal Wallis H test. The results showed that the total number of direct encounter points of long-tailed monkeys was 363 points. The highest number of direct encounter points for long-tailed monkeys was in period I (06/08 WITA) with a total of 160 points.The daily behavior frequency of long-tailed monkeys in the Forest Area of ​​Ranamese Resort, Ruteng Nature Tourism Park, East Manggarai Regency, East Nusa Tenggara Province, namely the behavior of moving / moving with a number of 973 (28%) followed by eating behavior 855 (25%), social 706 (21%), agonistic 269 (8%), grooming 251(7%), resting 233 (7%), sexual/mating 134 (4%), nesting 0 (0%). The most dominant behavior of moving/moving while the lowest behavior is making nests. The results of Kruskal Wallis' H test showed that there was a very significant difference between different types of behavior categories (P < 0.05).